Conocimientos y percepción sobre el tabaquismo y sus efectos dañinos a la salud entre los estudiantes adolescentes de Venecia y Aguas Zarcas, Costa Rica (UNED Research Journal, 2014)
Tobacco addiction represents one of the most grave worldwide public health problems, especially within populations of developing countries. Studies in Costa Rica and other countries demonstrate that this addiction frequently begins during adolescence. This study evaluated with a written questionnaire the general and specific knowledge of 529 students between the ages of 12 and 18 years of the health risks associated with tobacco addiction. It also evaluated their perceptions of the factors that predict the onset of adolescent tobacco addiction. The questionnaire was applied in three of the schools of Venecia and Aguas Zarcas, districts of the San Carlos canton of Costa Rica. The students demonstrated a basic knowledge of the health risks of tobacco addiction on the lungs, pregnancy complications, and cancer. The study indicated a lack of student knowledge of the adverse effects of tobacco on cardiovascular and female reproductive health. There existed a positive linear relation between median knowledge level and age (P≤0,0001; R2=5,45), as well as academic grade (P≤0,0001; R2=10,2). The predictive factors of adolescent tobacco addiction considered the most influential by the students were the influence of smokers within family and friend groups. The implementation of a comprehensive academic program for prevention of tobacco use and addiction that addresses both lack of knowledge and perceptions of these students related to tobacco addiction is recommended.
Keywords: tobacco addiction; smoking; health risks; adolescents; perceptions; San Carlos (Costa Rica)